(untitled) (Research, Society and Development, 2021)
Objective: to identify the scientific evidence, available in the literature, about the implementation and operationalization of Internal Regulation Centers in hospitals. Methodology: this is an integrative review, carried out in September 2020, in the LILACS, Pubmed and Scopus databases, using specific search strategies for each database. Of the 1028 studies found, 26 were selected for analysis. Results: The operationalization and implementation of the Internal Regulation Centers includes: bed management as a tool for access to health services; the work process for applying bed management in health services; and promoting bed management through operational tools. Conclusion: Knowledge of the evidence related to NIR assignments, problems and systematization allowed the composition of a structure to manage the flow of hospital beds, making this process clear and allowing to understand the construction of knowledge that underlies this process and the performance of professionals in hospital institutions.